Empowering EFL Teachers for Scientific Writing in PPG Workshop: Writing Classroom Action Research Proposal - Suhirman, Lalu; Rahayu, Budi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
The aims of this paper are (1) to Enhance EFL teachers’ professional competence and skill in writing scientific papers of research results; (2) to produce scientific articles of EFL teachers’ investigation (minimally produce an action research proposal). This workshop was given to Pendidikan Profesi Guru - PPG (Teacher Professional Education). There were 33 EFL English teachers actively participating in the workshop. The content of the materials was how to discover themes and topics, how to write a proposal of classroom action research (CAR), and how to compose research of CAR, then how to create it into a scientific article. By having these skills, it was expected that they were able to report or write their own CAR and how to create it into a scientific article so that raise their position and prosperity. The PPG workshop for CAR took 10 hours and at the end of the workshop, the participants (the EFL teachers) are obliged to submit a classroom action research. After evaluating each CAR proposal project submitted by the EFL teachers, almost all of them wrote the CAR proposal well. But, in certain components, not all participants’ CAR proposals were categorized good, as well as the bibliography and language components, for bibliography, the participants must include a minimum of 17 to 20 reference lists derived from books and journals which cited as references in the body of the proposal. There were 45.45% of participants who listed 17 references and 45.45% of participants listed 20 references, and the remaining 9.9% included less than 17 references. For language, all participants used Indonesian, their reasoning was to make them easier to express thoughts and ideas in the proposal. It was also found that 87,87% of EFL teachers stated that they were able to identify the research problems, themes, and topics well. While there were 66,66% of EFL teachers described that they were able to decide CAR design, theory, quote, and paraphrase experts’ ideas well and 90,90% of them stated 17 to 20 titles of references.